2023
DOI: 10.3390/ijms24087577
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Biomarkers in the Era of Immunotherapy for Lung Cancer

Abstract: The therapeutic algorithm of lung cancer has recently been revolutionized by the emergence of immune checkpoint inhibitors. However, an objective and durable response rate remains low with those recent therapies and some patients even experience severe adverse events. Prognostic and predictive biomarkers are therefore needed in order to select patients who will respond. Nowadays, the only validated biomarker is the PD-L1 expression, but its predictive value remains imperfect, and it does not offer any certaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 162 publications
(192 reference statements)
0
6
0
Order By: Relevance
“…Specifically, the PFS and OS were better in patients with high PD-L1 TPS (≥50%) than in those with low (1%–49%) or negative (<1%) PD-L1 TPS. 3 , 5 , 7 , 31 Although current efforts are intensely exploring potential predictive factors for chemoimmunotherapy, no definitive marker other than the PD-L1 TPS has been validated as predictors of chemoimmunotherapy response in advanced NSCLC without driver mutations. Several studies exploring TTF-1 expression status as a treatment response marker reported that the PFS and OS were significantly better in patients with TTF-1–positive tumors than in those with TTF-1–negative tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the PFS and OS were better in patients with high PD-L1 TPS (≥50%) than in those with low (1%–49%) or negative (<1%) PD-L1 TPS. 3 , 5 , 7 , 31 Although current efforts are intensely exploring potential predictive factors for chemoimmunotherapy, no definitive marker other than the PD-L1 TPS has been validated as predictors of chemoimmunotherapy response in advanced NSCLC without driver mutations. Several studies exploring TTF-1 expression status as a treatment response marker reported that the PFS and OS were significantly better in patients with TTF-1–positive tumors than in those with TTF-1–negative tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In the rapidly evolving landscape of cancer treatment, ICIs have emerged as a transformative approach, particularly in NSCLC [1,52,53,[59][60][61][62][63][64]. Nevertheless, the success of ICI treatment is closely intertwined with the identification of predictive biomarkers [65,66]. These biomarkers play a pivotal role in stratifying patients, guiding treatment decisions, and optimizing therapeutic outcomes.…”
Section: Possible Clinical Practice Implicationsmentioning
confidence: 99%
“…Among the main identified predictive markers, PD-L1 expression, tumor mutation burden (TMB), tumor-infiltrating lymphocytes (TILs), neutrophil/lymphocyte ratio (NLR), and specific genetic mutations emerged as established or potential tools to tailor ICIbased strategies for NSCLC patients [65,66]. The prognostic value of these biomarkers is summarized in Table 3.…”
Section: Predictive Biomarkers Of Ici Response In Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“…PD-L1 expression, along with tumor mutational burden and mismatch gene repair deficiency, has been validated as a predictive marker for ICI response and has received U.S. Food and Drug Administration (FDA) approval for companion diagnostics [ 11 ]. Other markers, such as tumor mutational burden and microsatellite instability, have also been recognized as predictive markers of ICI response [ 11 - 13 ]. However, the search for a perfect and reliable biomarker for ICI response is ongoing, and advanced molecular techniques are not readily available in many clinical situations.…”
mentioning
confidence: 99%